Comparative analysis on performance and emission characteristic of diesel engine fueled with heated coconut oil and diesel fuel - Hoang, A. T.; M. M., Noor; Pham, X. D. (Penerbit Universiti Malaysia Pahang, 2018)
Alternative fuel and renewable energy is becoming important issue due to unstable fuel supply and price. Recently, bio-fuels are much interested because of their beneficial effects on environment, agriculture and economic development. Raw vegetable oils – a kind of bio-fuels, even though it has many disadvantages, are potential renewable fuel replaced for ever-exhausted fossil fuel. In this work, vegetable oil available in the South of Vietnam such as raw coconut oil is used by heating up to aim at reducing its high viscosity, surface tension, density and meeting the fuel requirements. Experimental and comparative study is carried out on an 80 hp small marine diesel engine fueled with heated coconut oil (HCO) and fossil diesel fuel. The results of engine performance and emission characteristics are measured. The results show that, specific fuel consumption, CO, HC and smoke emissions are higher, but thermal efficiency and NOx emission are lower as using HCO in comparison with diesel fuel. Besides, this study also denotes that, heated raw coconut oil up to 100 oC is considered as the most proper fuel to achieve the engine performance and emission characteristics, which are equal to diesel fuel.